(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Two key elements that are continually considered when planning and carrying out staff responsibilities are layout and services. The interrelation between the two influences the attainment of a directed system toward its people. Researchers identified variables that may have an impact on the services provided inside 3s Center from Barangay Ugong, Valenzuela City. The purpose of this study was to assess the elements influencing the constituents' perception of the office layout at 3s Center in Barangay Ugong. Upon analyzing the data gathered in the study, the result shows a high level of satisfaction from the residents with regards to 3S Center Layout and its services. Locals are well guided by the indicators used to describe their perspective about the layout as well as their experience with the services. Hereof, the total weighted mean of 3.65 was attained to show the correlation between the two, and it proves that the layout certainly influences how the employee performs and carries out services. In general, Layout and Services are two significant things to consider for a quality office procedure. It was evident from the evaluation conducted by one of the 3S Centers from Valenzuela City. It revealed a high level of satisfaction from the residents that led to a better understanding and acceptance of innovative ways to use a system.